Strategies to Mitigate Supply Chain Disruptions During COVID-19: The Lived Experience of SC Professionals - Loo, Saw Khuan *; Shee, Himanshu Kumar; Tan, Suan See (The Laboratory of Logistics and Supply Chain Management, 2023)
Drawing on resource dependence theory (RDT), the objective of this study is to empirically explore supply chain disruptions of COVID-19, and suggest strategies to mitigate them. In-depth interviews were conducted with supply chain professionals working in the Electrical & Electronic (E&E) industry in Malaysia. Interviews were analyzed by following seven steps of the van Kaam method. Findings suggest six strategies: global command centre with daily planning cycle to mitigate component shortages; collaboration with suppliers to mitigate glove shortages; assist local suppliers in obtaining permits to mitigate disrupted manufacturing; dual sourcing to mitigate single-sourcing disruptions; collaboration with freight carriers and government agencies to mitigate disrupted freight; and ERP-integrated EDI to mitigate disrupted data sharing. The findings offer strategies for managers to de-risk their supply chains in post-COVID-19 era, and it could be applied further in similar future supply chain disruptions.